2012
DOI: 10.3390/metabo2040717
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the RelA Activity on E. coli Metabolism by Metabolite Profiling of Glucose-Limited Chemostat Cultures

Abstract: Metabolite profiling of E. coli W3110 and the isogenic ΔrelA mutant cells was used to characterize the RelA-dependent stringent control of metabolism under different growth conditions. Metabolic profiles were obtained by gas chromatography–mass spectrometry (GC-MS) analysis and revealed significant differences between E. coli strains grown at different conditions. Major differences between the two strains were assessed in the levels of amino acids and fatty acids and their precursor metabolites, especially whe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
9
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 51 publications
2
9
0
Order By: Relevance
“…Although it is not entirely understood how acetate overflow and the RelA-stringent control are connected, lower acetate levels in mutants suggest that the absence of the RelA-stringent control might reduce metabolic bottlenecks that ultimately lead to the accumulation of by-products, such as acetate. These results are also in agreement with metabolomics profiling analyses performed at the same conditions (Carneiro et al, 2012), where the accumulation of acetate and lactate, another metabolic by-product resulting from the metabolic overflow, was lower in mutant cultures. In this instance, we cannot state that alterations detected in protein ratios related to translation processes are caused by the gene mutation or a consequence of the reduced accumulation of acetate, but clearly the lack of the RelA activity induced profound alterations in many growth-related processes.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Although it is not entirely understood how acetate overflow and the RelA-stringent control are connected, lower acetate levels in mutants suggest that the absence of the RelA-stringent control might reduce metabolic bottlenecks that ultimately lead to the accumulation of by-products, such as acetate. These results are also in agreement with metabolomics profiling analyses performed at the same conditions (Carneiro et al, 2012), where the accumulation of acetate and lactate, another metabolic by-product resulting from the metabolic overflow, was lower in mutant cultures. In this instance, we cannot state that alterations detected in protein ratios related to translation processes are caused by the gene mutation or a consequence of the reduced accumulation of acetate, but clearly the lack of the RelA activity induced profound alterations in many growth-related processes.…”
Section: Discussionsupporting
confidence: 91%
“…Previous work on E. coli chemostat cultures (Carneiro et al, 2012) has shown that the RelA activity is growth rate-dependent and differently affects the metabolism of slow- and fast-growing cultures. As such, it is relevant to understand the influence of the RelA activity in the coordination of metabolic processes under different growth conditions.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The first version of MBROLE contained functional (biological) data on compounds from several public databases, including the Kyoto Encyclopedia of Genes and Genomes (KEGG) ( 9 ), the Human Metabolome Database (HMDB) ( 10 ), the Chemical Entities of Biological Interest (ChEBI) database ( 11 ) and the PubChem database (pubchem.ncbi.nlm.nih.gov). MBROLE has been used to analyse metabolomics experiments carried out in organisms such as human ( 12 ), rat ( 13 ), Escherichia coli ( 14 ), Thermobifida fusca ( 15 ), Synechococcus elongates ( 16 ), Phoenix canariensis ( 17 ) or Cordyceps bassiana ( 18 ).…”
Section: Introductionmentioning
confidence: 99%